Role of N-Glycosylation in FcγRIIIa interaction with IgG - Van Coillie, Julie; Schulz, Morten A.; Bentlage, Arthur E. H.; de Haan, Noortje; Ye, Zilu; Geerdes, Dionne M.; van Esch, Wim J. E.; Hafkenscheid, Lise; Miller, Rebecca L.; Narimatsu, Yoshiki; Vakhrushev, Sergey Y.; Yang, Zhang; et al. (Frontiers in Immunology, 2022)
Immunoglobulins G (IgG) and their Fc gamma receptors (FcγRs) play important roles in our immune system. The conserved N-glycan in the Fc region of IgG1 impacts interaction of IgG with FcγRs and the resulting effector functions, which has led to design of antibody therapeutics with greatly improved antibody-dependent cell cytotoxicity (ADCC) activities. Studies have suggested that also N-glycosylation of the FcγRIII affects receptor interactions with IgG, but detailed studies of the interaction of IgG1 and FcγRIIIa with distinct N-glycans have been hindered by the natural heterogeneity in N-glycosylation. In this study, we employed comprehensive genetic engineering of the N-glycosylation capacities in mammalian cell lines to express IgG1 and FcγRIIIa with different N-glycan structures to more generally explore the role of N-glycosylation in IgG1:FcRIIIa binding interactions. We included FcRIIIa variants of both the 158F and 158V allotypes and investigated the key N-glycan features that affected binding affinity. Our study confirms that afucosylated IgG1 has the highest binding affinity to oligomannose FcγRIIIa, a glycan structure commonly found on Asn162 on FcγRIIIa expressed by NK cells but not monocytes or recombinantly expressed FcγRIIIa.